2020
DOI: 10.1111/jocs.15147
|View full text |Cite
|
Sign up to set email alerts
|

ECMO therapy in COVID‐19: An experience from Zurich

Abstract: Background The current coronavirus disease 2019 (COVID‐19) pandemic has a huge impact on society and the economy and represents one of the biggest challenges for healthcare systems all over the world. Reports from healthcare institutions in different countries show a variety of crisis exit strategies. Methods The following is a review and update of the situation and crisis management in Zürich and Switzerland with a special focus on the impact on the cardiac surgery program and extracorporeal membrane oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…Seven studies reported data on COVID-19 patients suffering from two and more comorbidities (Figure 3). [18][19][20][21][22][23][24] COVID-19 patients requiring ECMO support with less than two comorbidities had lower mortality (23% vs 31%; OR 0.55; 95% CI 0.34-0.90; I 2 = 0%; P = .02) than those with two and more comorbidities. 12 cohorts contained comparative body mass index (BMI) data for COVID-19 survivors and nonsurvivors receiving ECMO support (Figure 2).…”
Section: Study Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Seven studies reported data on COVID-19 patients suffering from two and more comorbidities (Figure 3). [18][19][20][21][22][23][24] COVID-19 patients requiring ECMO support with less than two comorbidities had lower mortality (23% vs 31%; OR 0.55; 95% CI 0.34-0.90; I 2 = 0%; P = .02) than those with two and more comorbidities. 12 cohorts contained comparative body mass index (BMI) data for COVID-19 survivors and nonsurvivors receiving ECMO support (Figure 2).…”
Section: Study Characteristicsmentioning
confidence: 96%
“…[16][17][18][19][20][21][22][23][24][28][29][30][31] In 13 cohorts, the total duration of ECMO support received by COVID-19 patients was similar (mean 15.39 vs 16.62 days; SMD − 0.07; 95% CI [ − 0.30, 0.15];I 2 = 15%; P = .51) between survivors and nonsurvivors (Figure 4). [17][18][19][20][21][22][23][24][25][26][28][29][30] Respiratory Parameters Within 24 h Before ECMO Support Initiation…”
Section: Total Days On Mechanical Ventilation (Mv) Before Ecmo Support Initiation and Ecmo Durationmentioning
confidence: 98%
“… 3 The use of extracorporeal membrane oxygenation (ECMO) for patients with severe acute respiratory distress syndrome (ARDS) from COVID‐19 who have failed conventional mechanical ventilatory strategies has been described in multiple studies throughout the course of the pandemic. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 Besides limited reports in Europe that have described conflicting trends of patient outcomes on ECMO for COVID‐19 ARDS over the course of the pandemic, 12 , 13 , 14 little is known about the characteristics or trends between the eras of SARS‐CoV‐2 variants at their peak prevalence in the United States. The goal of this study is to describe the outcomes of patients who were placed on ECMO for severe COVID‐19 during different variants phases within a single healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the popularity of this topic is undoubtedly linked to the frequency of its clinical application. Further adding to the recent surge in the clinical literature is the trialing and adoption of ECMO as a therapy in some cases of severe Coronavirus disease 2019 (COVID-19) as a result of SARS-CoV2 infection [7][8][9]. Despite the increasing usage of ECMO, studies about ECMO are notably absent in the forensic literature.…”
Section: Discussionmentioning
confidence: 99%